(untitled) (World Economics and Finance Bulletin, 2023)
In this article, the socio-economic importance, principles and methods of improving the quality of household services, ways of effective use of resources in service enterprises, criteria determining the quality of household services, effective methods of comprehensive quality management, the essence and meaning of the concept of quality of household services, the life cycle of household services in the labor process, principles of quality management in the field and methods of determining quality in household service processes are researched.